Contesting the Leader on Daily Basis: Everyday Resistance and Nicolae Ceauşescu’s Cult of Personality - MARIN, Manuela (Studia Universitatis Babeș-Bolyai Historia, 2015)
My paper analyzes how a part of the Romanian people contested on daily basis their leader, Nicolae Ceausescu, and also the overwhelming presence of his cult of personality in their life especially during the 1980s. To this end, I will employ James C. Scott’s concept of everyday resistance in order to map the array of means used by the people in order to express their protest towards the public homage paid to the Romanian communist leader. My examination of the documents created by the Securitate (the former Romanian political police) and also by the Romanian department of Radio Free Europe, of the memoir literature published after the demise of the communist regime helped me to identify the following forms of everyday resistance towards Nicolae Ceausescu’s cult of personality: political discussions, individual or collective actions directed against the images of the Romanian communist leader, writing and spreading “documents containing hostile message” (unsigned letters, leaflets with messages against Nicolae Ceausescu) and political jokes. They will be analyzed from two main perspectives that will show and explain in what their resistance core lies in. The first one underlines that these forms of everyday resistance reversed the meanings of the homage assumptions made by the Romanian propaganda about Ceausescu’s leadership in order to identify what and particularly why certain aspects of his rule became the focus of the daily popular protest. The other perspective evaluates the role played by everyday resistance in the gradual undermining of Nicolae Ceausescu’s domestic legitimacy that along other evolutions led to the popular revolt against his rule in December 1989.